AN ANALYSIS OF USING ENGLISH IN CLASSROOM INTERACTION (A STUDY AT THE FIRST GRADE OF A PRIMARY SCHOOL) - Sri Supiah Cahyati (IKIP Siliwangi, 2018)
This research entitled: “An Analysis of Using English in Classroom Interactions (A Study at the First Grade of a Primary School)” to investigated the practice of using English in classroom interactions at the school. It is intended: 1) to identify and describe the teachers' and students' perceptions on the use of English in classroom interactions; 2) to identify, describe, and categorize the techniques of teaching English used by the teachers. The study reported here made use of qualitative research design as its method. It revealed that: all teachers and students regarded the practice of using English in classroom interactions as being useful in order to improve students’ English ability; in the practice of teaching English, teachers used various techniques and language exposures to students; the students’ achievement on the basis of the English syllabus shown that most of the targets in the syllabus were achieved and students could interact with teachers in simple English. However, there were some learning objectives that were not completely achieved, such as writing and reading words in English.